KONSEP GERAKAN KELUARGA SAKINAH DALAM PERSPEKTIF MUHAMMADIYAH - Nufus, Hayatun; Asqi, Hikmatul; Mardiana, Dina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The family is the most fundamental social institution, playing a crucial role in shaping individual character and community resilience. In the context of globalization and the digital era, families face various challenges, such as moral crises, communication disruption, and the negative influence of social media, which demand a family concept that is not only harmonious but also resilient and adaptive. This study aims to analyze the concept and implementation of the sakinah family movement from Muhammadiyah's perspective as a foundation for building a progressive civilization. This study used a qualitative method with a library research approach, reviewing various literature sources including books, scientific journals, articles, and official Muhammadiyah documents. Data were analyzed using thematic analysis techniques to identify the concept, principles, and implementation of the sakinah family within the context of modern life. The results show that Muhammadiyah, as a modern Islamic movement, has a strong commitment to building society through strengthening the family institution. The concept of the sakinah family from Muhammadiyah's perspective emphasizes not only harmony but also the integration of the values ​​of monotheism, justice, equality, and social responsibility. The sakinah family movement is realized through various development programs such as premarital guidance, Islamic parenting, economic empowerment, and family digital literacy. The implementation of this concept has proven effective in strengthening family resilience and shaping a generation with noble character and adaptability to changing times. Thus, a harmonious family becomes the primary foundation for building a civilized and progressive civilization.